Looking to draw: picturing the molecular body in art and science - Lookman, M (2014)
As a practice-led thesis comprised of drawing, sculpture, video, notebooks, and a written dissertation, this study by way of art making argues against the provocation that life sciences aided by the advances in visualizing techniques will hegemonise much of what there is to see and know about biological life. Historian James Elkins argued that non-art informational images were historically relevant considering the strategies scientists use for visualizing phenomena and W. J. T. Mitchell noted the impact of proliferation in image production together with computer technology as the epistemological shift from word to image and coined the phrase pictorial turn. Concurrently philosopher Gottfried Boehm deployed the term iconic turn to discuss the problematics associated with the power of images. I incorporate these insights to examine the affects of biomedical imaging as seen in artworks formed out of biologically sourced organic materials and techniques. Especially once grouped as Bio Art (Kac 1997) or organic media art (Hauser 2006) these artworks further accentuate the problem of representation and its relationship to knowledge and power underscored by the phenomena that biotechnology is changing perceptions of what the body is and can become. The written component of the thesis addresses these problems. It does this by critiquing visualization through the example fluorescent tagging as this technique exemplifies the most innovative and transgressive procedure for imaging biology in-vivo. I argue the following: the visualization of biology, like the mathematization of the surface of reflection pioneered by Ibn al-Haytham is not a problem because it shows Man’s technological prowess but rather because mathematization brings with it the legacy of ontological uneasiness with images in Western philosophical tradition. This tension persists and gets exacerbated especially in contexts where molecular scale visualizing aids the invention of novel life forms as art or laboratory creatures. To reconcile the paradoxes that emerge from critical analysis of the effects of biotechnology that have been discussed in binary terms such as natural or artificial, mimetic or real, I introduce to the lexicon of new media art and theory the concept of non-duality from Arabic philosophy formalized by Ibn ‘Arabi through the analogy of barzakh. In Ibn ‘Arabi’s scheme images are a part of the imaginal sphere and are not perceived as mimetic. Neither is the image given primacy in the formation of knowledge nor is the image given an absolute position of certainty. Instead, images are the intermediary and dynamic part of cognitive process that brings with reason knowledge and with knowledge, responsibility. Thus theorized, imaginal are able to facilitate the possibility to actualise the fullest comprehension of wujud that in translation is also the pursuit for knowledge that guides action. In this way informed by practice, this thesis dissolves the distrust of vision and proposes that scientific images are like art that can embolden the intellectual capacity for creativity and abstract thought.